Achieving Solution‐Processed Non‐Doped Single‐Emitting‐Layer White Organic Light‐Emitting Diodes through Adjusting Pyrene‐Based Polyaromatic Hydrocarbon. Issue 56 (8th August 2022) - Han, Hongjing; Hu, Sujuan; Zhang, Shilong; Li, Xiaojun; Sun, Hailing; Chen, Jiawen; Liu, Baiquan; Liu, Chuan; Chen, Wangqiao; Zhang, Qichun
Abstract: Single‐emitting‐layer white organic light‐emitting diodes (SEL‐WOLEDs) have developed rapidly in recent years due to the outstanding advantages of high efficiency, simple device structure, low cost, less phase separation, and stable emission color. Nevertheless, the relatively complicated host‐dopant system is usually essential for most previous SEL‐WOLEDs and the development of simple non‐doped SEL‐WOLEDs lags behind. Hence the straightforward synthesis of single‐white‐emitting molecules for non‐doped SEL‐WOLEDs still remains a great challengeable task. In this article, we designed and synthesized two new pyrene‐based polyaromatic hydrocarbons (PAHs) and used them as emitting layer materials in the OLED devices. When the molecules change from the mono‐fused one to bis‐fused one, the emitting light changes from greenish to white color. Further study indicated that the bis‐fused molecule PyD with more twisted and extended backbone packed in neat Cmca space group in single‐crystal system compared with P21 /n for PyS, which may be favorable to form excimers in the solid state and broaden the emission spectrum in the OLEDs. As a result, a solution‐processed non‐doped single‐white‐emitting‐molecule SEL‐WOLED with high performance (e. g., a high color rendering index of 66) is reported. The findings will be beneficial not only to further development of simple WOLEDs, but also to other related organic optoelectronic technology. Abstract : Two new pyrene‐based polyaromatic hydrocarbons (PAHs) molecules‐PyS and PyD were synthesized. Due to the more twisted and extended backbone, the bis‐fused molecule PyD packed in neat Cmca space group in single‐crystal system compared with P 21 / n for PyS, which may be favorable to form excimers in the solid state and showed solution‐processed non‐doped single‐white‐emitting‐molecule SEL‐WOLED with high performance.